Roles of Trees for Abatement of Environmental Pollution: A Review - P A, Clara Manasa; Salimath, Supriya K.; Hegde, Ramakrishna; Deepthi, Dechamma N. L.; Gooli, Manjunath (International Journal of Bio-resource and Stress Management, 2023)
Planet Earth has become inhospitable for the survival of biological species as it is facing the most serious threat from pollution. Forestation for the abatement of pollution and the betterment of the environment is a successful and widely accepted method among the many ways and means to mitigate environmental contamination. Pollutants are collected, assimilated, and stored by trees. The capacity of trees to capture and hold larger particulates on the epidermal and outer leaf surfaces aids in regulating dust pollution. Additionally, trees contribute to high-quality water by reducing soil erosion locally, which lowers silt in water bodies and traps or filters other water pollutants. In the context of noise pollution, trees can reduce 5-8 dB of noise per 100 feet of the forest by reflecting and absorbing sound energy. Utilizing live, green plants to lessen and/or remove toxins from contaminated soil, water, sediments, and the air is known as phytoremediation. Additionally, different types of genetically engineered trees have been developed through recombinant technologies, which can be utilized to remove heavy metals and toxic substances from contaminated sites. Such genetically modified or transgenic plants could help clean up contaminated sites by taking up pollutants using their roots. This review examines both the conventional and recent developments in using trees for bioremediating contaminated or polluted sites. Thus, by proper planting scheme with suitable species will bring healthy life and color to the cement concrete jungle of large congested cities